The In vitro efficacy of fungicides for control of Alternaria alternata on amaranth seeds (Semiárida, 2025)
In amaranth crop, Alternaria alternata (Fr.) Keissler is the causal agent leaf blight and a potential producer of mycotoxins that affect the quality of its seeds. With the aim of reducing the damage caused by A. alternata, assays were carried out in order to evaluate in vitro the effectiveness of Carboxin (20 % ai)+Thiram (20 % ai) 400, 500 and 600 ppm; Difenoconazole: (25 % ai) 250, 500 and 700 ppm and Copper sulfate pentahydrate (25 %) 250, 500 and 700 ppm on mycelial development and germination of conidia of A. alternata. The results obtained indicate that all fungicide concentrations inhibited the germination of A. alternata conidia between 80.13 to 92.54 %. Treatments with Carboxin+Thiram inhibited mycelial development between 69.45 to 72.30 %. Finally, the treatments Carboxin+Thiram (500 ppm), Difenoconazole (700 ppm) and Copper sulfate pentahydrate (500 ppm) were selected by: a) To inhibited mycelial growth of A. alternata (>39 %); b) To inhibit conidial germination of A. alternata (>82 %); c) To increase germination of amaranth seeds (>21 %); d) To reduce seed contamination of amaranth by A. alternata (>86 %) and (e) Were not phytotoxic for amaranth seeds and seedlings. Therefore, these results indicate that selected fungicides could be a suitable strategy to reduce the inoculum naturally present in amaranth seeds and therefore reduce the impact of the pathogen on the crop.
Keywords: foliar disease; strategy; mycelium growth; conidia; phytotoxicity